PENERAPAN METODE LANDSCAPE-URBANISM DALAM PERANCANGAN RUANG REKREASI KEBUGARAN DI SAWANGAN DEPOK - Glenn Geraldi; Tony Winata (Jurusan Arsitektur dan Perencanaan, 2021)
Inside Out: Sawangan Fitness Recreation Space is a project that aims to improve the quality of nutrition and the importance of healthy living behavior awareness in the midst of urban ecological density. Demographic condition of people entering their productive age (15-64 years) in 2020-2030 encourages the need for this project as part of the 'demographic bonus investment'. The population of urban environment is getting denser due to increasing urbanization. Acceleration of time and space makes urban environment less conducive to healthy physical activities and people are more easily exposed to obesogenic environments. Poor nutritional intake and lack of healthy living habits are problems that need to be solved. The concept is a balance between physical needs and mental needs that are obtained from the natural environment itself. This project is designed with landscape-urbanism method with beyond ecology parameter to implement landscape principals into urban environment which is expected to bring good health for urban communities. Keywords: fitness; healthyness; recreation; urban AbstrakInside Out: Ruang Rekreasi Kebugaran Sawangan merupakan proyek yang bertujuan untuk meningkatkan kualitas gizi dan kesadaran pentingnya perilaku hidup sehat di tengah kepadatan ekologi perkotaan. Kondisi demografi masyarakat memasuki usia produktif (15-64 tahun) di tahun 2020-2030 mendorong dibutuhkannya proyek ini sebagai bagian dari ‘investasi bonus demografi. Populasi lingkungan perkotaan semakin padat akibat peningkatan urbanisasi. Percepatan waktu dan ruang membuat lingkungan perkotaan tidak kondusif untuk aktivitas fisik yang menyehatkan dan masyarakat juga lebih mudah terpapar lingkungan obesogenik. Buruknya asupan gizi dan kurangnya perilaku hidup sehat menjadi permasalahan yang perlu diatasi. Konsep yang diusung adalah keseimbangan antara kebutuhan jasmani dan kebutuhan batin yang diperoleh dari lingkungan alam sendiri. Proyek ini dirancang dengan metode landscape-urbanism dengan parameter beyond ecology untuk mengintegrasikan prinsip lansekap ke dalam lingkungan perkotaan yang diharapkan membawa kebaikan bagi kesehatan masyarakat.